ANALISIS FAKTOR YANG MEMENGARUHI WALI MURID DALAM MENENTUKAN BIMBINGAN BELAJAR SERTA PENGARUHNYA TERHADAP BEBAN KOGNITIF SISWA SEKOLAH DASAR - Sabila Nur Khanifah; Dian Kusumawati; Rachmat Imam Muslim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the factors influencing parents in choosing tutoring services and their impact on elementary school students' cognitive load. This research uses a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation involving parents, students, and tutors. The results show that psychological factors are the most dominant in influencing parents’ decisions, especially expectations for children's academic improvement. Social and economic factors have less influence. Parents generally have positive perceptions of tutoring effectiveness, as it improves students’ understanding and learning motivation. Furthermore, tutoring does not significantly increase cognitive load, as students remain able to focus and maintain a balance between study and rest. However, emotional conditions and learning methods play an important role in managing students’ cognitive load. These findings indicate that proper instructional strategies are necessary to optimize learning outcomes without overloading students cognitively.